An ROR1 bi-specific T-cell engager provides effective targeting and cytotoxicity against a range of solid tumors. (3rd July 2017) - Gohil, Satyen Harish; Paredes-Moscosso, Solange Rosa; Harrasser, Micaela; Vezzalini, Marzia; Scarpa, Aldo; Morris, Emma; Davidoff, Andrew M.; Sorio, Claudio; Nathwani, Amit Chunilal; Della Peruta, Marco
ABSTRACT: We have developed a humanized bi-specific T-cell engager (BiTE) targeting receptor tyrosine kinase-like orphan receptor 1 (ROR1), a cell surface antigen present on a range of malignancies and cancer-initiating cells. Focusing initially on pancreatic cancer, we demonstrated that our ROR1 BiTE results in T cell mediated and antigen-specific cytotoxicity against ROR1-expressing pancreatic cancer cell lines in vitro at exceedingly low concentrations (0.1 ng/mL) and low effector to target ratios. Our BiTE prevented engraftment of pancreatic tumor xenografts in murine models and reduced the size of established subcutaneous tumors by at least 3-fold. To validate its wider therapeutic potential, we next demonstrated significant cytotoxicity against ovarian cancer in an in vitro and in vivo setting and T-cell-mediated killing of a range of histologically distinct solid tumor cell lines. Overall, our ROR1 BiTE represents a promising immunotherapy approach, because of its ability to target a broad range of malignancies, many with significant unmet therapeutic needs.